NIRS Hemodynamic Response to Methylphenidate in Children with Attention Aeficit Hyperactivity Disorder: First Administration, Titration Phase and Associations with Clinical Severity - A. Crippa; S. Grazioli; E. Rosi; M. Mauri; F. Villa; E. Maggioni; V. Diwadkar; P. Brambilla; M. Pozzi; M. Molteni; M. Nobile (European Psychiatry, 2022)
Introduction Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder characterized by lack of self-regulation and deficits in organizing behaviors in response to emotional stimuli. Methylphenidate (MPH) is one of the most effective psychostimulant drugs for ADHD, however, a possible predictive utility of brain hemodynamic data related to MPH administration and its relation to clinical symptomatology is still not clear. To address these questions, we used Near Infrared Spectroscopy (NIRS) technology, a non-invasive optical technique that allows to investigate the effect of psychopharmacological treatment on cortical hemodynamics.